Thermomechanical Joining of Hypoeutectic Aluminium Cast Plates - Borgert, Thomas; Neuser, Moritz; Hoyer, Kay-Peter; Homberg, Werner; Schaper, Mirko (Journal of Manufacturing and Materials Processing)
Consistent lightweight construction in the area of vehicle manufacturing requires the increased use of multi-material combinations. This, in turn, requires an adaptation of standard joining techniques. In multi-material combinations, the importance of integral cast components, in particular, is increasing and poses additional technical challenges for the industry. One approach to solve these challenges is adaptable joining elements manufactured by a thermomechanical forming process. By applying an incremental and thermomechanical joining process, it is possible to react immediately and adapt the joining process inline to reduce the number of different joining elements. In the investigation described in this publication, cast plates made of the cast aluminium alloy EN AC-AlSi9 serve as joining partners, which are processed by sand casting. The joining process of hypoeutectic AlSi alloys is challenging as their brittle character leads to cracks in the joint during conventional mechanical joining. To solve this, the frictional heat of the novel joining process applied can provide a finer microstructure in the hypoeutectic AlSi9 cast alloy. In detail, its Si is finer-grained, resulting in higher ductility of the joint. This study reveals the thermomechanical joining suitability of a hypoeutectic cast aluminium alloy in combination with adaptively manufactured auxiliary joining elements.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials

Auslegungsmethode zum Kleben höchstfester Stahlwerkstoffe im Landmaschinenbau - Göddecke, Johannes; Göhrs, Tim; Meschut, Gerson; Große Gehling, Manfred (Stahlbau)
Abstract In Konstruktionen des Landmaschinenbaus aus dickeren Blechen (ca. 3–10 mm) findet die Klebtechnik bislang nur wenig Anwendung, obwohl sie in anderen Einsatzgebieten bereits ein etabliertes Fügeverfahren darstellt und viele Vorteile gegenüber anderen Fügeverfahren bietet, da es bisher an Regelwerken bei der Auslegung derartiger Verbindungen fehlt. Ein wesentliches Kriterium bei der Auslegung von Verbindungen im Landmaschinenbau ist die Ermüdungsfestigkeit aufgrund der langen Nutzungsphase der Produkte und der in der Landtechnik vorherrschenden Belastungscharakteristika. Geklebte Verbindungen weisen ein hervorragendes Verhalten bei zyklischer Belastung auf. Die steigenden Anforderungen im Hinblick auf Ressourceneffizienz und Leichtbau führen zu einem Umdenken, da durch den vermehrten Einsatz höherfester Stahlwerkstoffe in Kombination mit der Klebtechnik dieses als umsetzbar erscheint. Ziel ist die Entwicklung einer Methode zur Auslegung geklebter Verbindungen in Konstruktionen mit höherfesten Stahlwerkstoffen in Anlehnung an die FKM‐Richtlinie. Die betriebsrelevanten Beanspruchungen der Landtechnik werden analysiert und an speziellen Probekörpern untersucht. Dabei werden sowohl die mechanischen, thermischen und medialen Einflussfaktoren als auch der Einfluss der Klebfugengeometrie und von Betriebslastenkollektiven untersucht. Die Erkenntnisse werden in einer KMU‐relevanten Vorgehensweise zur Ermittlung von Abminderungsfaktoren zusammengefasst, wodurch die Auslegung der Bauteilfestigkeit sowohl statisch als auch dynamisch möglich ist.
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials; Building and Construction; Civil and Structural Engineering

Measurement, Modelling, and Appli cation of Lubricant Properties at Extreme Pressures - Wingertszahn, Patrick; Schmitt, Sebastian; Thielen, Stefan; Oehler, Manuel; Magyar, Balázs; Koch, Oliver; Hasse, Hans; Stephan, Simon (Tribologie und Schmierungstechnik)
Lubricants play a central role in many technical applications, e.g. in bearings and gears as well as in machining processes. In such applications, lubricants are exposed to extreme conditions in the contact area. In lubrication gaps, the pressure can reach values up to 5 GPa. The thermophysical properties of lubricants, and in particular the viscosity, at such extreme conditions have an important influence on the friction and wear behavior of a tribosystem. Accordingly, reliable lubricant property models are a prerequisite for accurate tribological simulations, e.g. elastohydrodynamic lubrication (EHL) simulations. Presently, the vast majority of experimental thermophysical property data are only available up to 1 GPa. Thus, reliable and robust models with strong extrapolation capabilities to higher pressure are required. In this work, viscosity measurements of squalane in a temperature range be tween 20 °C and 100 °C and pressures up to 1 GPa were carried out. Based on that data, a physical model for the viscosity was developed. The model is built by combining a molecular-based equation of state with the so-called entropy scaling approach. Finally, we demonstrate how this fluid property model can be favorably integrated in an EHL simulation by an application programming interface (API). The novel hybrid modeling approach is promising for future applications.
Keywords: Surfaces; Coatings and Films; Surfaces and Interfaces; Mechanical Engineering; Mechanics of Materials

A new dual matrix burner for one-dimensional investigation of aerosol flames - Apazeller, Sascha; Gonchikzhapov, Munko; Nanjaiah, Monika; Kasper, Tina; Wlokas, Irenäus; Wiggers, Hartmut; Schulz, Christof (Proceedings of the Combustion Institute)
In spray-flame synthesis of nanoparticles, a precise understanding of the reaction processes is necessary to find optimal process parameters for the formation of the desired products. Coupling the chemistries of flame, solvent, and gas-phase species initially formed from the particle precursor in combination with the complex flow geometry of the spray flame means a special challenge for the modeling of the reaction processes. A new burner has been developed that is capable to observe the reaction of precursor solutions frequently used in spray-flame synthesis. The burner provides an almost flat, laminar, and steady flame with homogeneous addition of a fine aerosol and thus enables detailed investigation and modeling of the coupled reactions inde-pendent of spray formation and turbulent mixing. With its two separate supply channel matrices, the burner also enables the use of reactants that would otherwise react with each other already before reaching the flame. These features enable the investigation of a wide range of flame-based synthesis methods for nanoparticles and, due to the flat-flame geometry, kinetics models for these processes can be developed and validated. This work describes the matrix burner development and its gas flow optimization by simulation. Droplet-size dis-tributions generated by ultrasonic nebulization and their interaction with the burner structure are investigated by phase-Doppler anemometry. As an example for nanoparticle-for ming flames from solutions, iron-oxide nanoparticle-generating flames using iron(III) nitrate nonahydrate dissolved in 1-butanol were investigated. This effort includes measurements of two-dimensional maps of the flame temperature by a thermocouple and height-dependent concentration profiles of the main species by time-of-flight mass spectrometry. Exper-imental data are compared with 1D simulations using a reduced reaction mechanism. The results show that the new burner is well suited for the development of reaction models for precursors supplied in the liquid phase usually applied in spray-flame synthesis configurations.& COPY; 2022 The Combustion Institute. Published by Elsevier Inc. All rights reserved.
Keywords: Physical and Theoretical Chemistry; Mechanical Engineering; General Chemical Engineering

A new dual matrix burner for one-dimensional investigation of aerosol flames - Apazeller, Sascha; Gonchikzhapov, Munko; Nanjaiah, Monika; Kasper, Tina; Wlokas, Irenäus; Wiggers, Hartmut; Schulz, Christof (Proceedings of the Combustion Institute)
Keywords: Physical and Theoretical Chemistry; Mechanical Engineering; General Chemical Engineering

Influence of thermomechanical processing on the microstructural and mechanical properties of steel 22MnB5 - Reitz, A.; Grydin, O.; Schaper, M. (Materials Science and Engineering: A)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Size‐Dependent Strain Relaxation in InAs Quantum Dots on Top of GaAs(111)A Nanopillars - Riedl, Thomas; Kunnathully, Vinay S.; Trapp, Alexander; Langer, Timo; Reuter, Dirk; Lindner, Jörg K. N. (Advanced Materials Interfaces)
Keywords: Mechanical Engineering; Mechanics of Materials

Testing and modeling blast loading of a sandwich structure cored with a bio-inspired (balanus) core - Tuzgel, Firat; Akbulut Irmak, Emine Fulya; Guzel, Erkan; Yucesoy, Atacan; Sahin, Selim; Tasdemirci, Alper; Guden, Mustafa (Thin-Walled Structures)
Keywords: Mechanical Engineering; Building and Construction; Civil and Structural Engineering

Consideration of the manufacturing history of sheet metal components for the adaptation of a clinching process - Heyser, Per; Wiesenmayer, S; Frey, P; Nehls, T; Scharr, C; Flügge, W; Merklein, M; Meschut, Gerson (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
The process chain for the manufacturing of sheet metal components in mass production includes various cutting and forming operations, which influence the resulting properties of the parts and therefore subsequent manufacturing steps, such as clamping and joining. It is shown that clamping of the components leads to superimposed residual stresses and geometry changes. Therefore, the part properties differ from the initial state of the semifinished products, which has to be considered in the design of clinched joints. This paper presents an approach for coupled determination of the properties of semifinished and finished parts during deep drawing and clamping as well as their effects on the joint quality during clinching. One method for the effective and efficient determination of the properties of semifinished products and components during production is using process data from the preceding manufacturing processes, which is concretely presented in this work. In addition to the interconnection of the entire production chain, it is necessary to define relevant process data for each individual manufacturing step and to correlate the data with the material properties reliably. Therefore, the cross-process interactions of different steps of the process chain for the manufacturing of sheet metal components and the effect of process variations on subsequent manufacturing steps are investigated. Consequently, the boundary conditions for a mechanical joining process based on data from preceding process steps can be predicted.
Keywords: Mechanical Engineering; General Materials Science

Influence of hydrogel coatings on corrosion and fatigue of iron in simulated body fluid - Huang, Jingyuan; Voigt, Markus; Wackenrohr, Steffen; Ebbert, Christoph; Keller, Adrian; Maier, Hans Jürgen; Grundmeier, Guido (Materials and Corrosion)
Keywords: Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; Mechanical Engineering; Mechanics of Materials; Environmental Chemistry; Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; Mechanical Engineering; Mechanics of Materials; Environmental Chemistry; Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; Mechanical Engineering; Mechanics of Materials; Environmental Chemistry

Numerical and experimental identification of fatigue crack initiation sites in clinched joints - Ewenz, L.; Bielak, Christian Roman; Otroshi, Mortaza; Bobbert, Mathias; Meschut, Gerson; Zimmermann, M. (Production Engineering)
In this paper, a study based on experimental and numerical simulations is performed to analyze fatigue cracks in clinched joints. An experimental investigation is conducted to determine the failure modes of clinched joints under cyclic loading at different load amplitudes with single-lap shear tests. In addition, numerical FEM simulations of clinching process and subsequent shear loading are performed to support the experimental investigations by analyzing the state of stresses at the location of failure. An attempt is made to explain the location of crack initiation in the experiments using evaluation variables such as contact shear stress and maximum principal stress.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

Investigation of the influence of formed, non-rotationally symmetrical pin geometries and their effect on the joint quality of steel and aluminium sheets by direct pin pressing - Römisch, David; Kraus, Martin; Merklein, Marion (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
Resource-saving and sustainable production is becoming increasingly important regarding social, political and economic aspects, thus making the use of lightweight-construction technologies a current trend. For this reason, multi-material-systems made of high-strength steel and aluminium as well as metal and fibre-reinforced plastics gain in importance. However, different material properties, e.g. stiffness, thermal expansion coefficients or chemical incompatibilities, are challenging for conventional joining technologies. Joining by cold formed pin structures has shown to have high potential for joining multi-material-systems. These pins can be joined either by direct pin pressing into an unperforated joining partner or by caulking, where the pins are inserted through a pre-punched joining partner and the pin head is upset, resulting in a form-fit joint. Usually, cylindrical pins are used for joining. However, non-rotationally symmetrical pin geometries offer the possibility of introducing a predetermined breaking point or reinforcing a connection in the principal force direction. In this work, cylindrical pins as well as non-rotationally symmetrical pin geometries, such as polygonal and oval pin structures, are cold extruded from the sheet metal plane of an HCT590X+Z dual phase steel and joined in the next step with an EN AW-6014 aluminium using direct pin pressing. Since the formation of an undercut has an crucial influence on the joint strength, the investigations will be focused on the resulting joint geometry. In addition, the effect of different pin heights will be examined to analyse the joint formation at different levels of compression of the pin structures. Finally, the joints are evaluated regarding their joint strength in tensile shear tests and cross tension tests. Here the flow resistance of the geometry used as well as the pin height and thus the strain hardening of the pin base during the extrusion of the pins play a decisive role for the shear strength.
Keywords: Mechanical Engineering; General Materials Science

In-Mold-Assembly of Hybrid Bending Structures by Compression Molding - Stallmeister, Tim; Tröster, Thomas (Key Engineering Materials)
The further development of in-mold-assembly (IMA) technologies for structural hybrid components is of great importance for increasing the economic efficiency and thus the application potential. This paper presents an innovative IMA process concept for the manufacturing of bending loaded hybrid components consisting of two outer metal belts and an inner core structure made of glass mat reinforced thermoplastic (GMT). In this process, the core structure, which is provided with stiffening ribs and functional elements, is formed and joined to two metal belts in one single step. For experimental validation of the concept, the development of a prototypic molding tool and the manufacturing of hybrid beams including process parameters are described. Three-point bending tests and optical measurement technologies are used to characterize the failure behavior and mechanical properties of the produced hybrid beams. It was found that the innovative IMA process enables the manufacturing of hybrid components with high energy absorption and low weight in one step. The mass-specific energy absorption is increased by 693 % compared to pure GMT beams.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

A comparison of heuristic, statistical, and machine learning methods for heated tool butt welding of two different materials - Gevers, Karina; Tornede, Alexander; Wever, Marcel Dominik; Schöppner, Volker; Hüllermeier, Eyke (Welding in the World)
Abstract Heated tool butt welding is a method often used for joining thermoplastics, especially when the components are made out of different materials. The quality of the connection between the components crucially depends on a suitable choice of the parameters of the welding process, such as heating time, temperature, and the precise way how the parts are then welded. Moreover, when different materials are to be joined, the parameter values need to be tailored to the specifics of the respective material. To this end, in this paper, three approaches to tailor the parameter values to optimize the quality of the connection are compared: a heuristic by Potente, statistical experimental design, and Bayesian optimization. With the suitability for practice in mind, a series of experiments are carried out with these approaches, and their capabilities of proposing well-performing parameter values are investigated. As a result, Bayesian optimization is found to yield peak performance, but the costs for optimization are substantial. In contrast, the Potente heuristic does not require any experimentation and recommends parameter values with competitive quality.
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Fingerprints Indicating Superior Properties of Internal Interfaces in Cu(In,Ga)Se 2 Thin‐Film Solar Cells - Raghuwanshi, Mohit; Chugh, Manjusha; Sozzi, Giovanna; Kanevce, Ana; Kühne, Thomas; Mirhosseini, Hossein; Wuerz, Roland; Cojocaru‐Mirédin, Oana (Advanced Materials)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Corrosion Phenomena and Fatigue Behavior of Clinched Joints: Numerical and Experimental Investigations - Harzheim, Sven; Ewenz, Lars; Zimmermann, Martina; Wallmersperger, Thomas (Journal of Advanced Joining Processes)
Lightweight construction has increasingly become the focus of scientific research in recent years, not least due to the constantly increasing fuel price, which is a key factor in the economic viability of many companies. In this respect, the use of hybrid structures, made of dissimilar materials offers many advantages. However, such hybrid structures often have undesirable side effects. For example, brittle intermetallic phases are formed when aluminum and steel are welded. Clinching as a mechanical joining process does not produce such intermetallic phases since the connection is realized through form and force closure. In this process, a punch passes through two or more sheets and forms them into a permanent joint in a die. In the present work, the corrosion phenomena of an aluminum-steel clinched joint have been investigated by both experiments and numerical simulations in order to explain the superior fatigue behavior of pre-corroded joints. Therefore, the clinched joints have been corroded by a three-week salt-spray test. In addition, the electric potential and the von Mises stress are calculated under the assumption of a static loading. The results of both experiments and numerical simulations can explain the improvement in the fatigue behavior of the corroded specimens. This phenomenon can be attributed to the accumulation of corrosion products in small gaps between the joined metal sheets.
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Robustness Analysis of Pin Joining - Römisch, David; Zirngibl, Christoph; Schleich, Benjamin; Wartzack, Sandro; Merklein, Marion (Journal of Manufacturing and Materials Processing)
The trend towards lightweight design, driven by increasingly stringent emission targets, poses challenges to conventional joining processes due to the different mechanical properties of the joining partners used to manufacture multi-material systems. For this reason, new versatile joining processes are in demand for joining dissimilar materials. In this regard, pin joining with cold extruded pin structures is a relatively new, two-stage joining process for joining materials such as high-strength steel and aluminium as well as steel and fibre-reinforced plastic to multi-material systems, without the need for auxiliary elements. Due to the novelty of the process, there are currently only a few studies on the robustness of this joining process available. Thus, limited statements on the stability of the joining process considering uncertain process conditions, such as varying material properties or friction values, can be provided. Motivated by this, the presented work investigates the influence of different uncertain process parameters on the pin extrusion as well as on the joining process itself, carrying out a systematic robustness analysis. Therefore, the methodical approach covers the complete process chain of pin joining, including the load-bearing capacity of the joint by means of numerical simulation and data-driven methods. Thereby, a deeper understanding of the pin joining process is generated and the versatility of the novel joining process is increased. Additionally, the provision of manufacturing recommendations for the forming of pin joints leads to a significant decrease in the failure probability caused by ploughing or buckling effects.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials

Characterisation of Fibre Bundle Deformation Behaviour—Test Rig, Results and Conclusions - Borowski, Andreas; Gröger, Benjamin; Füßel, René; Gude, Maik (Journal of Manufacturing and Materials Processing)
Deformation of continuous fibre reinforced plastics during thermally-assisted forming or joining processes leads to a change of the initial material structure. The load behaviour of composite parts strongly depends on the resultant material structure. The prediction of this material structure is a challenging task and requires a deep knowledge of the material behaviour above melting temperature and the occurring complex forming phenomena. Through this knowledge, the optimisation of manufacturing parameters for a more efficient and reproducible process can be enabled and are in the focus of many investigations. In the present paper, a simplified pultrusion test rig is developed and presented to investigate the deformation behaviour of a thermoplastic semi-finished fiber product in a forming element. Therefore, different process parameters, like forming element temperature, pulling velocity as well as the forming element geometry, are varied. The deformation behaviour in the forming zone of the thermoplastic preimpregnated continuous glass fibre-reinforced material is investigated by computed tomography and the resultant pulling forces are measured. The results clearly show the correlation between the forming element temperature and the resulting forces due to a change in the viscosity of the thermoplastic matrix and the resulting fiber matrix interaction. In addition, the evaluation of the measurement data shows which forming forces are required to change the shape of the thermoplastic unidirectional material with a rectangular cross-section to a round one.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials

Pin Extrusion for Mechanical Joining from Orbital Formed Tailored Blanks with Local Material Pre-Distribution - Römisch, David; Hetzel, Andreas; Wituschek, Simon; Lechner, Michael; Merklein, Marion (Journal of Manufacturing and Materials Processing)
Pin extrusion is a common process to realise pin structures in different geometrical dimensions for a subsequent joining operation. Nevertheless, the process of pin extrusion offers process limits regarding sheet thinning as a consequence of the punch penetration depth into the sheet. Thereby, cracks at the residual sheet thickness can occur during strength tests, resulting in a failure of the complete joint due to severe thinning. Therefore, measures have to be taken into account to reduce the thinning. One possibility is the application of orbital formed tailored blanks with a local material pre-distribution, which allows a higher sheet thickness in the desired area. Within this contribution, the novel approach of a process combination of orbital forming and pin extrusion is investigated. To reveal the potential of a local material pre-distribution, conventional specimens are compared with previously orbital formed components. Relevant parameters such as the residual sheet thickness, the pin height as well as the average hardness values are compared. The results show a significant positive influence of a local material pre-distribution on the residual sheet thickness as well as the resulting pin height. Furthermore, the strain hardening during orbital forming can be seen as an additional advantage. To conclude the results, the process limits of conventional pin extrusion can be expanded significantly by the application of specimens with a local material pre-distribution.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials

Atomic Force Microscope with an Adjustable Probe Direction and Integrated Sensing and Actuation - Schaude, Janik; Hausotte, Tino (Nanomanufacturing and Metrology)
This article presents the application and evaluation of a cantilever with integrated sensing and actuation as part of an atomic force microscope (AFM) with an adjustable probe direction, which is integrated into a nano measuring machine (NMM-1). The AFM, which is operated in closed-loop intermittent contact mode, is based on two rotational axes that enable the adjustment of the probe direction to cover a complete hemisphere. The axes greatly enlarge the metrology frame of the measuring system by materials with a comparatively high coefficient of thermal expansion, which ultimately limits the achievable measurement uncertainty of the measuring system. Thus, to reduce the thermal sensitivity of the system, the redesign of the rotational kinematics is mandatory. However, in this article, some preliminary investigations on the application of a self-sensing cantilever with an integrated micro heater for its stimulation will be presented. In previous investigations, a piezoelectric actuator has been applied to stimulate the cantilever. However, the removal of the piezoelectric actuator, which is enabled by the application of a cantilever with an integrated micro heater, promises an essential simplification of the sensor holder. Thus, in the future it might be possible to use materials with a low coefficient of thermal expansion, which are often difficult to machine and therefore only allow for rather simple geometries. Furthermore, because of the creepage of piezoelectric actuators, their removal from the metrology frame might lead to improved metrological characteristics. As will be shown, there are no significant differences between the two modes of actuation. Therefore, the redesigned rotational system will be based on the cantilever with integrated sensing and actuation.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Materials Science (miscellaneous)

Comparison of two mesh-moving techniques for finite element simulations of galvanic corrosion - Harzheim, Sven; Hofmann, Martin; Wallmersperger, Thomas (Acta Mechanica)
Galvanic corrosion is a destructive process between dissimilar metals. The present paper presents a constructed numerical test case to simulate galvanic corrosion of two dissimilar metals. This test case is used to study the accuracy of different implementations to track the dissolving anode boundary. One technique is to numerically simulate a mesh displacement based on the prescribed displacement at the anode boundary. The second method is to adjust only the boundary elements. Re-meshing after a certain number of time steps is applied to both implementations. They produce similar results for an electrical and electrochemical field problem. This work shows that mesh smoothing does not result in higher accuracy when modeling a moving anode front. Adjusting only the boundary elements is sufficient when frequent re-meshing is used.
Keywords: Mechanical Engineering; Computational Mechanics

Investigations on Combined in situ CT and Acoustic Analysis during Clinching - Köhler, Daniel; Stephan, Richard; Kupfer, Robert; Troschitz, Juliane; Brosius, Alexander; Gude, Maik (Key Engineering Materials)
Clinching is a cost efficient method for joining components in series production. To assure the clinch point’s quality, the force displacement curve during clinching or the bottom thickness are monitored. The most significant geometrical characteristics of the clinch point, neck thickness and undercut, are usually tested destructively by microsectioning. However, micrograph preparation goes ahead with a resetting of elastic deformations and crack-closing after unloading. To generate a comprehensive knowledge of the clinch point’s inner geometry under load, in-situ computed tomography (CT) and acoustic testing (TDA) can be combined. While the TDA is highly sensitive to the inner state of the clinch point, it could detect critical events like crack development during loading. If such events are indicated, the loading process is stopped and a stepped in-situ CT of the following crack and deformation development is performed. In this paper, the concept is applied to the process of clinching itself, providing a detailed three-dimensional insight in the development of the joining zone. A test set-up is used which allows a stepwise clinching of two aluminium sheets EN AW 6014. Furthermore, this set-up is positioned within a CT system. In order to minimize X-ray absorption, a beryllium cylinder is used within the set-up frame and clinching tools are made from Si3N4. The actuator and sensor necessary for the TDA are integrated in the set-up. In regular process steps, the clinching process is interrupted in order to perform a TDA and a CT scan. In order to enhance the visibility of the interface, a thin tin layer is positioned between the sheets prior clinching. It is shown, that the test-set up allows a monitoring of the dynamic behaviour of the specimen during clinching while the CT scans visualize the inner geometry and material flow non-destructively.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Robust estimation of clinch joint characteristics based on data-driven methods - Zirngibl, Christoph; Schleich, Benjamin; Wartzack, Sandro (The International Journal of Advanced Manufacturing Technology)
Given a steadily increasing demand on multi-material lightweight designs, fast and cost-efficient production technologies, such as the mechanical joining process clinching, are becoming more and more relevant for series production. Since the application of such joining techniques often base on the ability to reach similar or even better joint loading capacities compared to established joining processes (e.g., spot welding), few contributions investigated the systematic improvement of clinch joint characteristics. In this regard, the use of data-driven methods in combination with optimization algorithms showed already high potentials for the analysis of individual joints and the definition of optimal tool configurations. However, the often missing consideration of uncertainties, such as varying material properties, and the related calculation of their impact on clinch joint properties can lead to poor estimation results and thus to a decreased reliability of the entire joint connection. This can cause major challenges, especially for the design and dimensioning of safety-relevant components, such as in car bodies. Motivated by this, the presented contribution introduces a novel method for the robust estimation of clinch joint characteristics including uncertainties of varying and versatile process chains in mechanical joining. Therefore, the utilization of Gaussian process regression models is demonstrated and evaluated regarding the ability to achieve sufficient prediction qualities.
Keywords: Industrial and Manufacturing Engineering; Computer Science Applications; Mechanical Engineering; Software; Control and Systems Engineering

Numerical fatigue life prediction of corroded and non-corroded clinched joints - Harzheim, Sven; Hofmann, Martin; Wallmersperger, Thomas (Mechanics of Advanced Materials and Structures)
Mechanical clinching is used to create lightweight hybrid structures. In order to estimate the service life of clinched components, its fatigue properties need to be known under different mechanical loading conditions. In addition to fatigue, corrosion is another factor that affects the fatigue life of clinched joints. In the literature, many corrosion and high-cycle fatigue damage models exist. However, little is known about how both phenomena interact in clinched joints. In this article, the influence of galvanic corrosion on clinched EN AW-6014/HCT590X + Z sheets on the fatigue life is investigated by means of numerical simulations and experimental results. An accurate prediction of the Wöhler lines of non-corroded and pre-corroded clinched specimens is shown.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science; General Mathematics; Civil and Structural Engineering

Size‐Dependent Strain Relaxation in InAs Quantum Dots on Top of GaAs(111)A Nanopillars - Riedl, Thomas; Kunnathully, Vinay; Trapp, Alexander; Langer, Timo; Reuter, Dirk; Lindner, Jörg (Advanced Materials Interfaces)
Keywords: Mechanical Engineering; Mechanics of Materials

Experimental and Numerical Investigation on Manufacturing-Induced Pre-Strain on the Load-Bearing Capacity of Clinched Joints - Bielak, Christian Roman; Böhnke, Max; Bobbert, Mathias; Meschut, Gerson (Key Engineering Materials)
Background. Clinching is a conventional cold forming process in which two or more sheets can be joined without auxiliary parts. A pre-forming of the parts to be joined, which is introduced by previous manufacturing steps, has an influence on the joining result. When considering the suitability for joining with regard to the formability of the materials, the influence of the preforming steps must be taken into account. The influences of strain hardening and sheet thickness on the joining properties must be investigated. In this context, a Finite Element Method (FEM) based metamodel analysis of the clinching process was carried out in [1] to investigate the robustness of the clinching process with respect to the different material pre-strains. In [2], the method was extended to the load bearing simulation.Procedure. The metamodel from preliminary work based on various FE models, which predicts the load-bearing capacity of a clinched joint influenced by pre-straining, is compared here with experimental data and the accuracy of the metamodel prediction is discussed. For this purpose an experimental procedure was further develop which allows the preforming of metal sheets from which joining specimens can be separated with a certain degree of unidirectional deformation. In the study, the procedure for preparing the joint specimens and the results of the loading tests are presented. Different possible relevant pre-strain combinations are investigated and compared with the simulation results, to validate the FE models and choose suitable metamodel.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Abnormal geodesics in 2D-Zermelo navigation problems in the case of revolution and the fan shape of the small time balls - Bonnard, B.; Cots, O.; Gergaud, J.; Wembe Moafo, Boris Edgar (Systems & Control Letters)
Keywords: Electrical and Electronic Engineering; Mechanical Engineering; General Computer Science; Control and Systems Engineering

Experimental and kinetic modeling study of the positive ions in premixed ethylene flames over a range of equivalence ratios - Knyazkov, Denis A.; Cherepanov, Andrey V.; Kiselev, Vitaly G.; Gerasimov, Ilya E.; Kasper, Tina; Shmakov, Andrey G. (Proceedings of the Combustion Institute)
Keywords: Physical and Theoretical Chemistry; Mechanical Engineering; General Chemical Engineering

Directional dependence of the mechanical properties of structural adhesive joints with curing-induced pre-deformations - Beule, Felix; Teutenberg, Dominik; Meschut, Gerson (Proceedings of the Institution of Mechanical Engineers, Part D: Journal of Automobile Engineering)
Owing to the implementation of multi-material construction methods in modern lightweight construction and the associated use of adhesive bonding technology, thermally induced relative displacements of the joining partners occur during the curing process. The resulting extremely complex thermo-chemo-mechanical stresses can influence the properties of the adhesive layers and reduce the load-bearing capacity. In this study, experiments are conducted to examine the influence of process-related thermal relative displacements on the mechanical properties of adhesives. The results show an anisotropy of the mechanical properties of the pre-deformed adhesive layers, depending on the magnitude and direction of the relative displacement.
Keywords: Mechanical Engineering; Aerospace Engineering

Kinetic investigation of the ozone-assisted partial oxidation of fuel-rich natural gas mixtures at elevated pressure - Kaczmarek, Dennis; Rudolph, Charlotte; Atakan, Burak; Kasper, Tina (Proceedings of the Combustion Institute)
Keywords: Physical and Theoretical Chemistry; Mechanical Engineering; General Chemical Engineering

A combustion chemistry study of tetramethylethylene in a laminar premixed low-pressure hydrogen flame - Bierkandt, Thomas; Hemberger, Patrick; Oßwald, Patrick; Gaiser, Nina; Hoener, Martin; Krüger, Dominik; Kasper, Tina; Köhler, Markus (Proceedings of the Combustion Institute)
Keywords: Physical and Theoretical Chemistry; Mechanical Engineering; General Chemical Engineering

Functionality Study of an Optical Measurement Concept for Local Force Signal Determination in High Strain Rate Tensile Tests - Böhnke, Max; Unruh, Eduard; Sell, Stanislaw; Bobbert, Mathias; Hein, David; Meschut, Gerson (Key Engineering Materials)
Many mechanical material properties show a dependence on the strain rate, e.g. yield stress or elongation at fracture. The quantitative description of the material behavior under dynamic loading is of major importance for the evaluation of crash safety. This is carried out using numerical methods and requires characteristic values for the materials used. For the standardized determination of dynamic characteristic values in sheet metal materials, tensile tests performed according to the guideline from [1]. A particular challenge in dynamic tensile tests is the force measurement during the test. For this purpose, strain gauges are attached on each specimen, wired to the measuring equipment and calibrated. This is a common way to determine a force signal that is as low in vibration and as free of bending moments as possible. The preparation effort for the used strain gauges are enormous. For these reasons, an optical method to determine the force by strain measurement using DIC is presented. The experiments are carried out on a high speed tensile testing system. In combioantion with a 3D DIC high speed system for optical strain measurement. The elastic deformation of the specimen in the dynamometric section is measured using strain gauges and the optical method. The measured signals are then compared to validate the presented method. The investigations are conducted using the dual phase steel material HCT590X and the aluminum material EN AW-6014 T4. Strain rates of up to 240 s-1 are investigated.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Strain mode-dependent weighting functions in hyperelasticity accounting for verification, validation, and stability of material parameters - Mahnken, Rolf (Archive of Applied Mechanics)
Abstract Optimized material parameters obtained from parameter identification for verification wrt a certain loading scenario are amenable to two deficiencies: Firstly, they may lack a general validity for different loading scenarios. Secondly, they may be prone to instability, such that a small perturbation of experimental data may ensue a large perturbation for the material parameters. This paper presents a framework for extension of hyperelastic models for rubber-like materials accounting for both deficiencies. To this end, an additive decomposition of the strain energy function is assumed into a sum of weighted strain mode related quantities. We propose a practical guide for model development accounting for the criteria of verification, validation and stability by means of the strain mode-dependent weighting functions and techniques of model reduction. The approach is successfully applied for 13 hyperelastic models with regard to the classical experimental data on vulcanized rubber published by Treloar (Trans Faraday Soc 40:59–70, 1944), showing both excellent fitting capabilties and stable material parameters.
Keywords: Mechanical Engineering

Goal-oriented error estimation and h-adaptive finite elements for hyperelastic micromorphic continua - Ju, Xiaozhe; Mahnken, Rolf; Xu, Yangjian; Liang, Lihua (Computational Mechanics)
Keywords: Applied Mathematics; Computational Mathematics; Computational Theory and Mathematics; Mechanical Engineering; Ocean Engineering; Computational Mechanics

Physics informed neural networks for continuum micromechanics - Henkes, Alexander; Wessels, Henning; Mahnken, Rolf (Computer Methods in Applied Mechanics and Engineering)
Keywords: Computer Science Applications; General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; Computational Mechanics

“Red Carbon”: A Rediscovered Covalent Crystalline Semiconductor - Odziomek, Mateusz; Giusto, Paolo; Kossmann, Janina; Tarakina, Nadezda V.; Heske, Julian; Rivadeneira, Salvador M.; Keil, Waldemar; Schmidt, Claudia; Mazzanti, Stefano; Savateev, Oleksandr; Perdigón‐Toro, Lorena; Neher, Dieter; et al. (Advanced Materials)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

C 1 N 1 Thin Films from Guanine Decomposition Fragments - Jerigová, Mária; Heske, Julian; Kühne, ThomasD.; Tian, Zhihong; Tovar, Michael; Odziomek, Mateusz; Lopez Salas, Nieves (Advanced Materials Interfaces)
Keywords: Mechanical Engineering; Mechanics of Materials

“Red Carbon”: A Rediscovered Covalent Crystalline Semiconductor - Odziomek, Mateusz; Giusto, Paolo; Kossmann, Janina; Tarakina, Nadezda V.; Heske, Julian Joachim; Rivadeneira, Salvador M.; Keil, Waldemar; Schmidt, Claudia; Mazzanti, Stefano; Savateev, Oleksandr; Perdigón‐Toro, Lorena; Neher, Dieter; et al. (Advanced Materials)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Stimulation and Enhancement of Near‐Band‐Edge Emission in Zinc Oxide by Distributed Bragg Reflectors - Kothe, Linda; Albert, Maximilian; Meier, Cedrik; Wagner, Thorsten; Tiemann, Michael (Advanced Materials Interfaces)
The free exciton transition (near-band-edge emission, NBE) of ZnO at ≈388 nm can be strongly enhanced and even stimulated by an underlying photonic structure. 1D Photonic crystals, so-called distributed Bragg reflectors, are utilized to suppress the deep-level emission of ZnO (DLE, ≈500–530 nm). The reflector stacks are fabricated in a layer-by-layer procedure by wet-chemical synthesis. They consist of low-ε porous SiO2 layers and high-ε TiO2 layers. Varying the thickness of the SiO2 layers allows tuning the optical bandgap in a wide range between ≈420 and 800 nm. A ZnO layer is deposited on top of the reflector stacks by sol–gel synthesis. The spontaneous photoluminescence (PL) emission of the ZnO film is modulated by the photonic structure. When the optical bandgap of the reflector is in resonance with the deep-level emission of ZnO (DLE, ≈500–530 nm), then this defect-related emission mode is suppressed. Strong NBE emission is observed even when the ZnO layer does not show any NBE emission (due to low crystallinity) in the absence of the photonic structure. With this cost-efficient synthesis method, emitters for, e.g., luminescent gas sensors can be fabricated.
Keywords: Mechanical Engineering; Mechanics of Materials

The Structure of Water in Silica Mesopores – Influence of the Pore Wall Polarity - Weinberger, Christian; Zysk, Frederik; Hartmann, Marc; Kaliannan, Naveen; Keil, Waldemar; Kühne, Thomas; Tiemann, Michael (Advanced Materials Interfaces)
In the spatial confinement of cylindrical mesopores with diameters of a few nanometers, water molecules experience restrictions in hydrogen bonding. This leads to a different behavior regarding the molecular orientational freedom (‘structure of water') compared to the bulk liquid state. In addition to the pore size, the behavior is also strongly affected by the strength of the pore wall-to-water interactions, that is, the pore wall polarity. In this work, this is studied both experimentally and theoretically. The surface polarity of mesoporous silica (SiO2) is modified by functionalization with trimethylsilyl moieties, resulting in a change from a hydrophilic (pristine) to a hydrophobic pore wall. The mesopore surface is characterized by N2 and H2O sorption experiments. Those results are combined with IR spectroscopy to investigate pore wall-to-water interactions leading to different structures of water in the mesopore. Furthermore, the water's structure is studied theoretically to gain deeper insight into the interfacial interactions. For this purpose, the structure of water is analyzed by pairing densities, coordination, and angular distributions with a novel adaptation of surface-specific sum-frequency generation calculation for pore environments.
Keywords: Mechanical Engineering; Mechanics of Materials

Geometric and mechanical joint characterization of conventionally and tumbled self-piercing riveting joints - Wituschek, Simon; Kappe, Fabian; Meschut, Gerson; Lechner, Michael (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
In view of economic and ecological trends, the concepts for lightweight construction in transport systems are becoming increasingly important. These are frequently applied in the form of multi-material systems, which are characterized by the selective use of materials and geometries. One major challenge in the manufacturing of multi-material systems is the joining of the individual components to form a complete system. Mechanical joining processes such as semi-tubular self-piercing riveting are frequently used for this application but reach their limits concerning the number of combinations of geometry and material. In order to react to the requirements and to increase the versatility of semi-tubular self-pierce riveting, a process combination consisting of a tumbling process and a self-pierce riveting process has been presented previously. This process combination is used in this work to investigate the versatility and to identify the influencing parameters on it. For this purpose, experiments are conducted to identify process-side influence possibilities. The tests are performed with a dual-phase steel aluminum alloy to represent the varying mechanical characteristics of multi-material systems. Furthermore, the initial sheet thicknesses of the joining partners are varied in several steps. In addition to the geometric joint formation used to describe the undercut, the rivet head end position and the residual sheet thickness, the joining process, is also analyzed during the investigations. Further, the innovative joining process is evaluated by comparing it with a conventional self-piercing riveting process. The knowledge obtained represents a basis for the identification and evaluation of the versatility of the process combination.
Keywords: Mechanical Engineering; General Materials Science

Review on mechanical joining by plastic deformation - Meschut, Gerson; Merklein, M.; Brosius, A.; Drummer, D.; Fratini, L.; Füssel, U.; Gude, M.; Homberg, Werner; Martins, P.A.F.; Bobbert, Mathias; Lechner, M.; Kupfer, R.; et al. (Journal of Advanced Joining Processes)
Mechanical joining technologies are increasingly used in multi-material lightweight constructions and offer opportunities to create versatile joining processes due to their low heat input, robustness to metallurgical incompatibilities and various process variants. They can be categorised into technologies which require an auxiliary joining element, or do not require an auxiliary joining element. A typical example for a mechanical joining process with auxiliary joining element is self-piercing riveting. A wide range of processes exist which are not requiring an auxiliary joining element. This allows both point-shaped (e.g., by clinching) and line-shaped (e.g., friction stir welding) joints to be produced. In order to achieve versatile processes, challenges exist in particular in the creation of intervention possibilities in the process and the understanding and handling of materials that are difficult to join, such as fiber reinforced plastics (FRP) or high-strength metals. In addition, predictive capability is required, which in particular requires accurate process simulation. Finally, the processes must be measured non-destructively in order to generate control variables in the process or to investigate the cause-effect relationship. This paper covers the state of the art in scientific research concerning mechanical joining and discusses future challenges on the way to versatile mechanical joining processes.
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Geometric and mechanical joint characterization of conventionally and tumbled self-piercing riveting joints - Wituschek, Simon; Kappe, Fabian; Meschut, Gerson; Lechner, Michael (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
In view of economic and ecological trends, the concepts for lightweight construction in transport systems are becoming increasingly important. These are frequently applied in the form of multi-material systems, which are characterized by the selective use of materials and geometries. One major challenge in the manufacturing of multi-material systems is the joining of the individual components to form a complete system. Mechanical joining processes such as semi-tubular self-piercing riveting are frequently used for this application but reach their limits concerning the number of combinations of geometry and material. In order to react to the requirements and to increase the versatility of semi-tubular self-pierce riveting, a process combination consisting of a tumbling process and a self-pierce riveting process has been presented previously. This process combination is used in this work to investigate the versatility and to identify the influencing parameters on it. For this purpose, experiments are conducted to identify process-side influence possibilities. The tests are performed with a dual-phase steel aluminum alloy to represent the varying mechanical characteristics of multi-material systems. Furthermore, the initial sheet thicknesses of the joining partners are varied in several steps. In addition to the geometric joint formation used to describe the undercut, the rivet head end position and the residual sheet thickness, the joining process, is also analyzed during the investigations. Further, the innovative joining process is evaluated by comparing it with a conventional self-piercing riveting process. The knowledge obtained represents a basis for the identification and evaluation of the versatility of the process combination.
Keywords: Mechanical Engineering; General Materials Science

Review on mechanical joining by plastic deformation - Meschut, G.; Merklein, M.; Brosius, A.; Drummer, D.; Fratini, L.; Füssel, U.; Gude, M.; Homberg, W.; Martins, P.A.F.; Bobbert, M.; Lechner, M.; Kupfer, R.; et al. (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Further Development of an Adaptive Joining Technique Based on Friction Spinning to Produce Pre-Hole-Free Joints - Wischer, Christian; Homberg, Werner (Key Engineering Materials)
Mechanical joining processes are an essential part of modern lightweight construction. They permit materials of different types to be joined in a way that is suitable for the loads involved. These processes reach their limits, however, as soon as the boundary conditions change. In most cases, these elements are specially adapted to the joining point and cannot be used universally. Changes require cost-intensive adaptation of both the element and the process control, thus making production more complex. This results in high costs due to the increased number of auxiliary joining element variants required and reduces the economic efficiency of mechanical joining. One approach to overcoming this issue is the use of adaptive auxiliary joining elements formed by friction spinning. This article presents the current state of research on pre-hole-free joining with adaptive joining elements. The overall process chain is illustrated, explained and analyzed. Special attention is paid to demonstrating the feasibility of pre-hole-free joining with adaptive joining elements. The chosen mechanical parameters are subsequently listed. Finally, a comprehensive outlook of the future development potential is derived.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

A Review on the Modeling of the Clinching Process Chain - Part III: Operational Phase - Schramm, Britta; Harzheim, Sven; Weiß, Deborah; Joy, Tintu David; Hofmann, Martin; Mergheim, Julia; Wallmersperger, Thomas (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Development of a method for the separate measurement of the growth of internal crack tips by means of the potential drop method - Kullmer, Gunter; Weiß, Deborah; Schramm, Britta (Engineering Fracture Mechanics)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

A statistically based strain energy function for polymer chains in rubber elasticity - Mahnken, Rolf; Mirzapour, Jamil (Archive of Applied Mechanics)
Keywords: Mechanical Engineering

Mechanical joining in versatile process chains - Meschut, Gerson; Merklein, Marion; Brosius, Alexander; Bobbert, Mathias (Production Engineering)
The use of mechanical joining technologies offers the possibility of joining mixed material structures, which are used in particular in lightweight construction. An integrated securing of the joinability in versatile process chains is currently hardly possible as the number of combinable tool variants as well as variable force- and path-based process parameters is infinite. A versatile process chain, i.e. a sequence of all the processes and process steps required for product manufacturing, enables targeted changes to the semi-finished product, the joint, the component or the joining process that exceed the originally planned extend while still ensuring joinability. In detail, it leads to a unique joint with its own mechanical property profile, which, against the background of the resulting infinite number of combinations, makes it impossible to secure the joinability on the conventional experimentally based approach without extensive safety factors. The Transregional Colaborative Research Center 285 (TCRC285), which also initiated this special issue, is intended to enable mechanical joining technology to be versatile in the sense of high application flexibility. This is to be achieved with a numerical representation of the complete process chain from the incoming semi finished product via the joining part production and the joining process to the property profile of the joint in the operating phase. Thus a predictability of the joinability can be achieved and improvements in the individual life cycles of a joint can be realized by grasping the cause-and-effect relationships. On the basis of this knowledge, new possibilities for intervention in the joining process are to be created for the adaptation of the joining processes. With the aid of the methods developed for this purpose, tools will later be available to the end user to substitute the large number of mechanical joining processes or joining task-specific configurations with a smaller number of adaptable processes. This expands the flexibility in material choices, enabling challenges in environmental issues and sustainability to be overcome.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

Electron–Nuclear Coherent Coupling and Nuclear Spin Readout through Optically Polarized VB– Spin States in hBN - Murzakhanov, Fadis F.; Mamin, Georgy Vladimirovich; Orlinskii, Sergei Borisovich; Gerstmann, Uwe; Schmidt, Wolf Gero; Biktagirov, Timur; Aharonovich, Igor; Gottscholl, Andreas; Sperlich, Andreas; Dyakonov, Vladimir; Soltamov, Victor A. (Nano Letters)
Keywords: Mechanical Engineering; Condensed Matter Physics; General Materials Science; General Chemistry; Bioengineering